Personal trainer - occupational choices determinants - Leśniewska, Aleksandra (Journal of Education, Health and Sport, 2017)
Fitness service market is currently dynamically growing in Poland. As a result fitness services portfolio is rapidly broadening and clients interest in that matter escalates as well, therefore personal trainers profession seemed to be a great opportunity of employment for fitness enthusiasts nowadays. The main purpose of this study was to identify personal trainers occupational choices as there is very little publications in the field. For that purpose diagnostic survey with individual in-depth interviews among working personal trainers was conducted. Respondents stated that among many determinants the most important were: highly profitable job, easy access to the profession in Poland, independence and flexibility, interpersonal relations with clients, work as a passion and further professional opportunities.